Model of Adjudicatory Powers of Polish Administrative Courts (Contemporary Central & East European Law, 2024)
The issue of the shape of adjudicatory powers of administrative courts (cassation or substantive) is currently one of the most important research areas of the European doctrine devoted to judicial control of administration. These issues are currently being discussed in Poland, which translates into changes in the legislation regulating judicial-administrative procedure. The purpose of this article is to present, to a foreign reader, what the Polish model of judicial control of public administration currently looks like in terms of adjudicatory competences of administrative courts, with particular emphasis on the power to rule on the merits by administrative courts. In order to synthesise the issue in question, firstly the process of development of these competences is presented against the background of regulations of individual procedural acts. It is followed by a presentation of the reasons why the Polish adjudication model is supplemented with competences which make it possible for administrative courts to adjudicate on the merits. Then practical and doctrinal problems linked to a given adjudication model are dealt with. The conclusion of the article contains a summary of the above considerations, coupled with an attempt to fit the Polish adjudication model into the author’s scheme of models currently found in Europe. The discussion ends with a forecast of further development of the presented model.